If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + 3) + 4x = 0 Reorder the terms: (3 + x)(x + 3) + 4x = 0 Reorder the terms: (3 + x)(3 + x) + 4x = 0 Multiply (3 + x) * (3 + x) (3(3 + x) + x(3 + x)) + 4x = 0 ((3 * 3 + x * 3) + x(3 + x)) + 4x = 0 ((9 + 3x) + x(3 + x)) + 4x = 0 (9 + 3x + (3 * x + x * x)) + 4x = 0 (9 + 3x + (3x + x2)) + 4x = 0 Combine like terms: 3x + 3x = 6x (9 + 6x + x2) + 4x = 0 Reorder the terms: 9 + 6x + 4x + x2 = 0 Combine like terms: 6x + 4x = 10x 9 + 10x + x2 = 0 Solving 9 + 10x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (9 + x)(1 + x) = 0Subproblem 1
Set the factor '(9 + x)' equal to zero and attempt to solve: Simplifying 9 + x = 0 Solving 9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + x = 0 + -9 x = 0 + -9 Combine like terms: 0 + -9 = -9 x = -9 Simplifying x = -9Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {-9, -1}
| -6y-12=-60 | | 4t+16=24 | | -29n=2233 | | 6(y+3)=12y | | 4(x+2)=3(x-3)+x | | -8x-7=57 | | 2n+3+6(n-7)=5n-6 | | -(x+2)-2=3x-4-4x | | 18=8x-9-5x | | 5+3b=23 | | -18=-3-x | | -6(-2y+6)-3=6+1(-6y+9) | | 1+2a=11 | | 3+2v=11 | | -5x+18=18 | | 1+9(x-1)-6(2x+2)=2x+5 | | 12-4n-2(n-1)=4(n+4) | | 2(4-6x)+8=38-2(x+1) | | -36-2x=-7(x+8) | | x+6=12-x | | 11x-51=6x-1 | | 5+2(z-2)-6(4z+3)=20z+4z | | 12+5x=52 | | 15=5k-3+3 | | x-1=3x | | x^2=18-3x | | 7x-5y=7 | | 5x+7y=8 | | x^2=18x-3x | | 7-10x=123-38x | | 49x-35y= | | 49x-35y=21 |